On experimental designs, differencial learning, theoretical issues, dynamical systems, and the capability to adapt: Response to Schöllhorn - Hossner, E.-J.; Käch, B.; Enz, J. (Human Movement Science, 2016)
On experimental designs, differencial learning, theoretical issues, dynamical systems, and the capability to adapt: Response to Schöllhorn The comments made by Wolfgang Schöllhorn on our paper on the optimal degree of fluctuations in motor learning provides us with the opportunity to add some clarifications to our arguments. These clarifications pertain to (i) the rationale of our experiments, (ii) the relevance of our findings for the differencial-learning (DL) approach, (iii) theoretical issues with the DL concept, (iv) the value of a dynamical-systems perspective in the context of the debate at hand, and to (v) miscellaneous further points that deserve nuancing.